Cancer Surveillance Guideline for individuals with PTEN hamartoma tumour syndrome - Tischkowitz Marc; Colas Chrystelle; Pouwels Sjak; Hoogerbrugge Nicoline; PHTS Guideline Development Group & The European Reference Network GENTURIS (NATURE PUBLISHING GROUP, 2022)
PTEN hamartoma tumour syndrome is a diverse multi-system disorder predisposing to the development of hamartomatous growths, increasing risk of breast, thyroid, renal cancer, and possibly increasing risk of endometrial cancer, colorectal cancer and melanoma. There is no international consensus on cancer surveillance in PHTS and all current guidelines are based on expert opinion. A comprehensive literature review was undertaken and guidelines were developed by clinicians with expertise from clinical genetics, gynaecology, endocrinology, dermatology, radiology, gastroenterology and general surgery, together with affected individuals and their representatives. Recommendations were put forward for surveillance for breast, thyroid and renal cancers. Limited recommendations were developed for other sites including endometrial, colon and skin. The proposed cancer surveillance recommendations for PHTS require a coordinated multidisciplinary approach and significant patient commitment. The evidence base for cancer surveillance in this guideline are limited, emphasising the need for prospective evaluation of the effectiveness of surveillance in the PHTS population.